Nontargeted screening method for veterinary drugs and their metabolites based on fragmentation characteristics from ultrahigh-performance liquid chromatography-high-resolution mass spectrometry. (1st February 2022) - Liang, Wenying; Zheng, Fujian; Chen, Tiantian; Zhang, Xiuqiong; Xia, Yueyi; Li, Zaifang; Lu, Xin; Zhao, Chunxia; Xu, Guowang
Graphical abstract: Highlights: An in-house drug MS/MS database was constructed with 3, 710 drugs and their metabolites. Fragmentation characteristics of parent drugs and drug metabolites were summarized. The nontargeted screening method was developed to discover unknown drugs. In a demonstration application, 4 veterinary drugs and 3 drug metabolites were defined in egg. Abstract: Nontargeted screening of both veterinary drugs and their metabolites is important for comprehensive safety evaluation of animal-derived foods. In this study, a novel nontargeted screening strategy was developed for veterinary drugs and their metabolites based on fragmentation characteristics from ultrahigh-performance liquid chromatography–high-resolution mass spectrometry. First, an in-house database of mass spectra including 3, 710 veterinary drugs and their metabolites was constructed. Second, fragmentation characteristics of parent drugs and their metabolites in mass spectrometry were investigated and summarized. Then, a nontargeted screening procedure was established based on fragmentation characteristics to screen unknown parent drugs and their metabolites. Finally, the strategy was applied to 33 egg samples, and four veterinary drugs and three drug metabolites were determined and identified. These results showed that the developed strategy can realize suspect and nontargeted screening of veterinary drugs and their metabolites, and can also be applied to other animal-derived foods.